Metode Dakwah Melalui Lembaga Masjid Studi Kasus Masjid Al-Muttaqin Tuban - Kahfi, Shofiyullahul; Rahmat Albustomi, Abdul (Department of Da'wah Management, Faculty of Da'wah, IAINU Tuban, 2025)
The method of preaching is an effective way to explain strategically identified preaching. In this case, preaching in the mosque is not only limited to Friday sermons or sermons, but also involves various activities that can strengthen faith and increase religious knowledge of Muslims. Linguistic definition of technique The term